2015
DOI: 10.1037/a0037485
|View full text |Cite
|
Sign up to set email alerts
|

The big-fish-little-pond effect: Generalizability of social comparison processes over two age cohorts from Western, Asian, and Middle Eastern Islamic countries.

Abstract: Extensive support for the seemingly paradoxical negative effects of school-and class-average achievement on academic self-concept (ASC)-the big-fish-little-pond effect (BFLPE)-is based largely on secondary stu dents in Western countries or on cross-cultural Program for International Student Assessment studies. There is little research testing the generalizability of this frame of reference effect based on social comparison theory to primary school students and or to matched samples of primary and secondary stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
84
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 112 publications
5
84
1
2
Order By: Relevance
“…While there is currently some evidence that supports the assumption of negative BFLP effect already in the primary school context, more research is needed to establish whether these findings could be replicated in other educational systems. Furthermore, previous findings by Marsh et al (2015) suggest replications of the BFLP effect would be especially relevant in Nordic countries where the effect might be different if compared to other Western countries. Thus, in the present study, data from students in grade 3 (age 9), grade 4 (age 10), and grade 6 (age 12) were used to examine whether the assumptions of the BFLP effect model already hold during the primary school years in Finland.…”
Section: The Big-fish-little-pond Effect Modelmentioning
confidence: 95%
See 3 more Smart Citations
“…While there is currently some evidence that supports the assumption of negative BFLP effect already in the primary school context, more research is needed to establish whether these findings could be replicated in other educational systems. Furthermore, previous findings by Marsh et al (2015) suggest replications of the BFLP effect would be especially relevant in Nordic countries where the effect might be different if compared to other Western countries. Thus, in the present study, data from students in grade 3 (age 9), grade 4 (age 10), and grade 6 (age 12) were used to examine whether the assumptions of the BFLP effect model already hold during the primary school years in Finland.…”
Section: The Big-fish-little-pond Effect Modelmentioning
confidence: 95%
“…These studies have shown a particularly strong negative effect of classroom performance among all students attending academically selective schools or classes (Marsh and Hau 2003). The BFLP effect model has seldom been studied in nonselective educational settings, and more specifically, only a few researchers (Guo et al 2018;Marsh et al 2015;Pinxten et al 2015) have studied it in nonselective primary school systems, in which the present study was conducted.…”
Section: The Big-fish-little-pond Effect Modelmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, Marsh, Chessor, Craven, and Roche (1995) showed that the BFLPE occurs in samples of children between 9 and 11 years old regardless of their sex, age, and initial ability. In a recent study conducted in a nationally representative sample of 4th-and 8th-grade students from 13 different countries comprising 117,321 students from 6499 classes (TIMSS study), Marsh et al(2014) demonstrated developmental and cross-cultural generalizability of the BFLPE on math self-concept. Based on these previous results and theory, we expected the BFLPE to be significant in this study comprising a sample of children between 8 and 11 years old.…”
Section: Developmental Effects On the Bflpementioning
confidence: 99%